Generation Cycle of Jebba Hydro Power Plant and its Effect on the National Power Grid (Journal of Basic and Applied Research in Biomedicine, 2022)
This paper presents the trend of power generation for the Jebba hydro-power plant and its effect on the Nigerian National Power Grid (NPG). Since electricity is used on a 24-hour basis, it is requiredto bestable and constantly available.However, it has been observed that there is usually a shortfall between the actual and available generated output power of hydro-power plants. Four years of power generation data (2003 – 2006) was analyzed to establish this trend.The data was acquired from hourly, daily, weekly and yearly inspection reading sheets of synchronous generators. The components of the data used include; the average available capacity (MW), the average actual generation (MW), the number of operational hours in a month, the total outage period (hours), the in-service period (hours), the reservoir computed inflow (m3) and the total water discharge (m3). It was observed that the power plant is only able to generate about 75% of its installed capacity for only two months (October and November) but less at the other months of the year. Positive correlations exist between the reservoir computed inflow (m3), total water discharge (m3) and the average actual generation. Tables and statistical charts were used to analyze the station’s performance, and recommendations for improved performance was made. This study has established a trend of power generation which can be used for power generation planning for Nigeria to enable a constant supply of electricity.